KUALITAS SEMAI DAN SISTEM PERAKARAN STEK PUCUK DAN OKULASI JATI PADA BERBAGAI UKURAN KONTINER DI PERSEMAIAN HUTAN WANAGAMA I - , ANIFFAH NUR AZIZAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The correct size of container is one of way to prepare a long-term higher quality seed needs in terms of increasing productivity. It is expected that the right size of container could improve the quality of teak seedlings and cuttings root systems and bud grafting so it can be a consideration in the selection of the size of container in an operational scale. The purpose of this study was to determine the effect of variations in container size to the quality of teak seedlings from cuttings propagation and bud grafting, as well as to determine the effect of variations in container size to teak root system from the cuttings and bud grafting. The Research uses 3 different treatment of container size on teak seedlings and cuttings bud grafting which were the large size with 15 cm x 18 cm (322,45 ml), medium size container with 12 cm x 18 cm (206,37 ml) and the small size with 10 cm x 15 cm (119,43). Each treatments use 10 replication with each replication consist of 3 stems of seedlings, so there were 6 combinations of treatment with the 180 rods of planted cuttings and bud grafting implanted for 6 months. Growth variabel that were observed were seedling height, seedling diameter, number of leaves, number of roots, root lenght, root diameter, dry weight, robustness, top root ratio, biomass and seed quality. The trend of data were analyzed with Microsof Excel 2007. The results showed that the use of the larger container increased the height growth, diameter, canopy dry weight, roots, seedlings, seedling biomass, robustness, quality of teak cuttings and bud grafting and top root ratio (T/R) relatively uniform at the age of 6 months of teak seedlings. The large size container with 15 cm x 18 cm (322,45 ml) and medium size container with 12 cm x 18 cm (206,37 ml) indicates the root system teak cuttings and bud grafting that is better than the small container 10 cm x 15 cm (119,43 ml).